Attachment-Related Differences in Emotion Regulation in Adults: A Systematic Review on Attachment Representations - Dirk W. Eilert; Anna Buchheim (Brain Sciences, 2023)
In recent years, there has been an increase in the prevalence of mental disorders connected with affective dysregulation and insecure attachment. Therefore, it is even more important to understand the interplay between an individual’s attachment representation and patterns of emotion regulation. To our knowledge, this is the first systematic review to examine this association. PsycInfo, PsyArticles, and PubMed were searched for studies that examined attachment-related differences in emotion regulation in adults. To examine the unconscious attachment representation, only studies using the Adult Attachment Interview or the Adult Attachment Projective Picture System were included. Thirty-seven peer-reviewed studies (with a total of 2006 subjects) matched the PICO criteria. Emotion regulation was measured via four objective approaches: autonomic nervous system, brain activity, biochemistry, or nonverbal behavior. Across all measurements, results reveal a significant correlation between attachment representation and emotion regulation. Secure attachment correlates consistently with balanced emotion regulation, whereas it is impaired in insecure and dysfunctional in unresolved attachment. Specifically, unresolved individuals display counterintuitive responses and fail to use attachment as a resource. Insecure-dismissing attachment is associated with an emotionally deactivating strategy, while on a physiological, biochemical, and nonverbal level, emotional stress is still present. There is still a lack of studies examining preoccupied individuals. In addition to interpreting the results, we also discuss the risk of bias, implications for psychotherapy and coaching, and an outlook for future research.